Is it possible to achieve a "fit" of management control practices and strategies in Indonesia's reformed public hospitals? - Nurkholis Nurkholis; Endang Mardiati; Nurul Fachriyah; Made Aristia Prayudi; Nanda Widaninggar (Journal of Accounting and Investment, 2023)
Research aims: This research aims to investigate the effectiveness of implementing management control practices (MPCs) and examine whether MPC is possible and how MPCs as a package "fit” with the strategic choices of Local Community Service Agency (BLUD) public hospitals (PHs) in Indonesia.Design/Methodology/Approach: This study applied mixed-method research with a sequential explanatory strategy. Quantitative data were collected through self-administered questionnaires distributed to 29 top management team members of eight BLUD PHs in East Java and Bali, Indonesia. Meanwhile, qualitative data were generated by conducting a semi-structured interview with four selected top management team members of BLUD PHs. The data were then analyzed quantitatively and qualitatively by implementing profile deviation analysis, cluster analysis, ordinal regression analysis, and content analysis.Research findings: Quantitatively, the researchers found a negative correlation, yet insignificant, between the “misfit” of MCPs and strategy and management control effectiveness. Thus, the “fit” hypothesis was not supported. Qualitatively, the researchers revealed that BLUD PHs extensively used MCPs and employed them in various ways, including cultural, administrative, and dominantly cybernetic controls. Finally, it can be concluded that using cybernetic controls as a dominant practice is unsuitable for the strategy chosen by BLUD PHs in Indonesia.Practical and Theoretical contribution/Originality: This study expands upon what has already been explored in the management control literature concerning how MCPs might be configured to align with organizational strategy, especially in the context of public healthcare organizations. Practically, the reformed PHs in Indonesia are expected to understand better the structure and characteristics of the BLUD-based financial management environment. It is essential for organizations, as it helps them figure out exactly how their management control practices and organizational strategies fit together.Research limitation: Due to the low questionnaire and interview participation, mixed-methods research was underutilized in this study.